LEARNING STYLE AND ITS IMPACTS ON LEARNING FROM TERTIARY STUDENTS’ PERCEPTION: A SURVEY - Shariffuddin, Sara Asmawati; Tarmizi , Muhammad Luqman Haziq Mohd; Shamsuri, Muhammad Fakrulrazi Ahmad; Jalil, Abdul Haadi Muttaqin Abdul; Azmi, Iaiman Ilyas; Zainal, Muhammad Muttaqin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Negative educational outcomes have been linked to the incompatibility between learners’ learning styles and teachers’ teaching methods, such as decreased student engagement, reduced motivation to learn, and lower academic performance. Even though tremendous focus has been given to student-centered learning in tertiary education, limited research is available pertaining to the learning preferences of technical students on the East Coast of Malaysia. Therefore, this study examines students’ preferred learning styles at a technical tertiary institution in Terengganu to better understand how learning styles vary across academic backgrounds. The study also investigates students’ perceptions of the alignment of their favored learning methods and the lecturers’ instructional strategies. A quantitative research approach was applied, whereby 112 students completed a Google Forms survey. The data then was analyzed using descriptive statistical analysis. The results reveal that the majority favored hands-on tasks, watching audiovisual content, and group collaboration, implying these approaches foster deeper learning. The study contributes to the literature by understanding preferred learning methods among technical tertiary students and how they respond pedagogical mismatch.